2020
DOI: 10.1002/aoc.5907
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically recoverable 2‐(aminomethyl)phenols‐modified nanoparticles as a catalyst for Knoevenagel condensation and carrier for palladium to catalytic Suzuki coupling reactions

Abstract: A class of magnetic nanoparticles modified by 2-(aminomethyl)phenols has been successfully designed and synthesized as a reusable catalyst for Knoevenagel reaction. What's more, such nanomaterial also proved as suitable carrier for immobilization of palladium nanoparticles and the obtained composite exerted potent catalytic activity in Suzuki coupling reactions. Both of the (aminomethyl)phenols-modified nanoparticles and its related palladium nanocatalyst could be easily separated and reused for several consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…11 Knoevenagel condensations are accomplished under base 12 and acid-catalyzed 13 protocols. Recently, new catalysts such as triphenylphosphine, 14 nano-composites, 15 MOF, 16 and COF 17 have also been demonstrated as effective for such conversions. Most of these reactions exploit the basic nature of the catalyst to accelerate the conversion.…”
Section: Introductionmentioning
confidence: 99%
“…11 Knoevenagel condensations are accomplished under base 12 and acid-catalyzed 13 protocols. Recently, new catalysts such as triphenylphosphine, 14 nano-composites, 15 MOF, 16 and COF 17 have also been demonstrated as effective for such conversions. Most of these reactions exploit the basic nature of the catalyst to accelerate the conversion.…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 Also, composites containing metal oxides showed high reactivity as heterogeneous catalysts for Knoevenagel condensation, and the metal oxides in these composites were prior chemically modified or doped with metals. 14 17 …”
Section: Introductionmentioning
confidence: 99%
“…Because of these limitations, many efforts have been devoted in this area to find alternative routes to perform this reaction under base-free conditions. Previous studies have reported the use of different heterogeneous catalysts containing zeolites, mesoporous silica, ionic liquids, and graphitic carbon nitride. , Also, composites containing metal oxides showed high reactivity as heterogeneous catalysts for Knoevenagel condensation, and the metal oxides in these composites were prior chemically modified or doped with metals. …”
Section: Introductionmentioning
confidence: 99%
“…However, the fabrication of availably zinc ferrite-supported copper catalyst (Cu/ZnFe 2 O 4 ) should settle the following intrinsic obstacles: 1) the di culty of possessing both high catalytic activity and good magnetic properties because of the fact that the catalytic active copper is prone to be wrapped by the surrounding catalytically inactive magnetic materials; 2) the stability of the materials under reaction conditions, such as high temperature, pH, organic corrosion and so on; 3) issues associated with the catalytic activities and catalytic e ciency. Considering the importance of developing e cient heterogeneous catalysts for degradation of aromatic nitro compounds and C-N bond formation reactions, together with our continuous investigation on the application and development of magnetically recoverable materials [22], herein we wish to report a novel Cu/ZnFe 2 O 4 composite material as e cient catalyst for both of the above mention reactions. This developed composite features easy availability, high catalytic performance, and good reusability via a simple magnetic separation method.…”
Section: Introductionmentioning
confidence: 99%